Intestinal Parasites among school children (7 to 12 years) in rural areas of Kudat District Sabah Malaysia - Daw Khin Saw Naing; Tin, Tin Myint; Khin, Swe Oo; Khebir Verasahib (Universiti Malaysia Sabah, 2008)
Parasitism is the relationship between two species in which one benefits at the expense of the other [1}. Worms are common parasites of human beings. Protozoa and worms are common intestinal parasites in rural settings where the level of sanitation is substandard. Among the common intestinal parasites, soil-transmitted helminthiases (STHs) collectively cause the highest global burden of parasitic disease after malaria and are most prevalent in the poorest communitiesI2). In 1999, WHO estimated that schistosomiasis and soil transmitted helminths represented more than 40% of the disease burden due to all tropical diseases, excluding malaria (3). Soil-transmitted helminthiases (STHs) are intestinal nematodes (Ascaris lumbricoides, Trichuris trichiura and the hookworms Ancylostoma duodenale and Nicator americanus) Infecting humans and are included in the World Health Organization list of Neglected Tropical Diseases[2). This STH infection is now posing a health threat to developing nations due to Its large health burden. It Is estimated by WHO In 2002 that nearly 2000 million people worldwide would be affected by soil transmitted helminths (STH) {4]. In China alone, it is estimated to have 194 million people infected with STH {5J.